Influence of Different Obstetric Factors on Early Postpartum Pelvic Floor Function in Primiparas After Vaginal Delivery - Chi X; Yu S; Zhu K; Chen Y; Chu Y; Chen X (International Journal of Women's Health, 2023)
Xiaolei Chi,1,2,* Shushu Yu,1,2,* Kun Zhu,3 Yiyao Chen,1,2 Yi Chu,1,2 Xinliang Chen1,2 1Department of Obstetrics and Gynecology, International Peace Maternity and Child Health Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Shanghai Key Laboratory of Embryo Original Disease, Shanghai, People’s Republic of China; 3Department of Pathology, Tenth People’s Hospital of Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinliang Chen, Tel +8618017316169, Fax +86(21)64071243, Email superstarcxl@126.comPurpose: This study sought to explore the obstetric factors affecting early postpartum pelvic floor function of primiparas after vaginal delivery.Patients and Methods: We included 3362 primiparas who underwent postpartum re-examination in International Peace Maternity and Child Health Hospital at 42– 60 days after delivery. The Glazer Protocol was used to evaluate their pelvic floor function, and univariate and multivariate logistic regression analyses were performed to identify obstetric factors that might affect it.Results: Forceps-assisted delivery significantly increased the risk of the decline in fast- and slow-twitch muscle strength in the early postpartum period when compared with natural vaginal delivery (P < 0.05). Women with a pre-pregnancy body mass index (BMI) of ≥ 18.5 kg/m2 had a decreased risk of decline in fast-twitch muscle strength than those with a pre-pregnancy BMI of < 18.5 kg/m2 (P < 0.05). Women who had a pre-pregnancy BMI of 24.0 to < 28.0 kg/m2 bore a decreased risk of decline in slow-twitch muscle strength than those with a pre-pregnancy BMI of < 18.5 kg/m2 (P < 0.05). The risk of decline in fast-twitch muscle strength and slow-twitch muscle in women with anemia during pregnancy was significantly increased (P < 0.05); women with second-stage labors of > 2 h had an increased risk of fast-twitch and slow-twitch muscle strength decline than those with < 2 h (P < 0.05).Conclusion: Both pre-pregnancy underweight and obesity may cause impairment of early postpartum pelvic floor function. Forceps delivery, anemia during pregnancy, and the length of second stage of labor are independent factors leading to pelvic floor function impairment.Keywords: surface electromyography, Glazer Protocol, anemia during pregnancy, forceps delivery, the second stage of labor, body mass index